ضفاف جاسم محمد الحسيني عزل وتشخيص البكتريا لممرضه من مناطق جسميه مختلفه من المرضى في محافظة الديوانيه - ضفاف جاسم (University of Thi-Qar Journal of Science, 2019)
The current study included the seperation and identification of bacteria that causes inflamedcases from 1/8 August to 15 / 9 September . It was gathered (135 samples) including (95) samples for paitients. Including tonsilite, ear, nose,eye and wounds swab. The pathalogical samples were collected from the patients in the consulting infirmary in AlDiwanya general hospital .The normal samples were collected from the patient s companious in Al-Diwanya city.Both samples were for different ages and sexes. Special tests about the isolated bacteria were excuted to show the ability of this bacteria of producing some enzymes (positiv or negative ) Gram,s stain , bacteria was diagnosed depending on the test results IMVIC and dignosis (20)samples from tonsilites swab appear bacteria Streptococci pyogenes ratio( %65) it was followed bacteria Staph. aureus in ratio (%35) while number isolated dignosis from swab (ear, wounds, eye and nose) They were(13,11,30,21) samples in sequence that showed the spread of bacteria Proteus mirabilis in ratio (%57.14), Pseudomonas aeruginosa in ratio (%28.57) and isolate bacteria Klebsiella pneumonia in ratio (%14.28) isolated bacteria from ear while isolated bacteria from wounds it was Staph. aureus to in ratio (%60) followed Escherichia. Coli in ratio (%40) while bacteria isolated from eye it was followed represented Staph. aureus ,Staph. epidermidis  Corynebacterium. diphtheroid in ratio (%9.09, 36.36,54.54) in sequnce the spread of bacteria Pseudomonas aeruginosa it was followed Haemophilus spp in ratio (%38.46,61.53) all it either isolated bacteria from healthy persons as control groupe it was Escherichia. Coli in high ratio (%52.5) it was followed Staph. aureus in low ratio it found inhealthy personal in ratio (%10) only different aereas in body . It was showed Staph. aureus high sensetive to Streptomycin antibiotic in ratio (%89.66) while resisted Tetracycline in ratio (%62.06) while Staph. epidermidis it was high sensetivity to Ampicillin in ratio (%83.34) while resisted Neomycin antibiotic in ratio (%66) while Streptococci bacteria was sevsetivie in ratio (%92.37) to cefotaxime antibiotic while resisted Neomycin in ratio (%53.84)While Escherichia. Coli bacteria it was sensetive to cefotaxime antibiotic in ratio (%75) while resisted Ampicillin in ratio (%83.33). Showed Klebsiella pneumonia high resisted to Cefotaxime antibiotic in ratio (%100) while Corynebacterium. diphtheroid bacteria appear high resisted to all Ceftazidime,Streptomycin,Trimethprim,Rifampicin,Ampicillin in ratio (%100). either  Haemophillus bacteria it was sensetive to Neomycin antibiotic in ratio (%60) and it was resisted  to Streptomycin antibiotic in ratio (%80) while appear Pseudomonas aeruginosa bacteria high sensetivity to Cefotaxime antibiotic in ratio (%85.75) while resisted Ceftazidime antibiotic inratio (%78.57).